2002
DOI: 10.1177/10778010222182937
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Gender Inequality on Female Homicide Victimization Across U.S. Cities

Abstract: To expand our understanding of gender inequality and violent crime, this study provides an assessment of the relationship between gender inequality and lethal violence against women. The authors use a cross-sectional design with racially disaggregated census data for 158 large U.S. cities in 1990 to assess the degree to which women's absolute status and their status relative to men affect their risk of homicide victimization. Overall, the findings suggest that although certain measures of women's absolute and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 38 publications
4
66
1
1
Order By: Relevance
“…While there is no doubt a confluence of structural factors that affect homicide, research has shown that the status of females has important implications for a variety of types of homicide [4,36,50,51,54]. Homicide [8] studies employing gender stratification as the explanatory framework are typically concerned with the victimization of women.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…While there is no doubt a confluence of structural factors that affect homicide, research has shown that the status of females has important implications for a variety of types of homicide [4,36,50,51,54]. Homicide [8] studies employing gender stratification as the explanatory framework are typically concerned with the victimization of women.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…There are a few exceptions to this approach in some recent work. These studies have attempted to use multiple indicators of patriarchy (DeWees and Parker 2003;Heimer 2000;Parker and Reckdenwald 2008;Steffensmeier and Haynie 2000;Vieraitis et al 2007;Vieraitis and Williams 2002;Whaley and Messner 2002;Straus 1984, 1990), however, these studies still fall short of a thorough operationalization of patriarchy because again they focus primarily on economic measures. As Vieraitis et al (2007, p. 61) note ''Although all feminist theories argue that macro-level variables such as absolute deprivation and structural inequality are important, there is currently no consensus on the direction these relationships should take.''…”
Section: Socialist Feminism and Criminologymentioning
confidence: 97%
“…Most of the published research that deals with aspects of gender inequality tends to focus on a single dimension of gender inequality and employs either a single measure operationalizations of the construct (see review by Bradley and Khor 1993) or a set of variables that tap such social dimensions as educational status, employment, poverty or political participation (Brewer and Smith 1995;DeWees and Parker 2003;Vieraitis and Williams 2002;Young et al 1994). Few attempts have been made to develop a measure for assessing gender inequality in different spheres simultaneously.…”
Section: Gender Inequality and Its Measurementmentioning
confidence: 98%
“…The macrosystem sources of gender inequality directly affect both aggregate rates of violence and an individual woman's risk of becoming the victim of partner violence (Dobash and Dobash 1979;Smith 1990;Straus 1994;Yllo and Straus 1990). It also influences her risk of suffering health problems, especially those related to sexual health including AIDS (Lawson 1999), of experiencing poverty, unemployment and unhealthy employment conditions (Rice 2001), homicides (Baron and Straus 1988;DeWees and Parker 2003;Titterington 2006;Vieraitis and Williams 2002), rape and sexual violence (Austin and Kim 2000;Yodanis 2004), and more.…”
mentioning
confidence: 97%